2018 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP) 2018
DOI: 10.1109/icassp.2018.8462229
|View full text |Cite
|
Sign up to set email alerts
|

Distributed Splitting-Over-Features Sparse Bayesian Learning with Alternating Direction Method of Multipliers

Abstract: In processing spatially distributed data, multi-agent robotic platforms equipped with sensors and computing capabilities are gaining interest for applications in inhospitable environments. In this work an algorithm for a distributed realization of sparse bayesian learning (SBL) is discussed for learning a static spatial process with the splitting-over-features approach over a network of interconnected agents. The observed process is modeled as a superposition of weighted kernel functions, or features as we cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Consequently, the algorithm converges fast while having a fixed communication load on the network. As we will show, using simulations and real data studies, the proposed algorithm performs on par with the centralized versions in terms of normalized mean squared error (NMSE) and parameter sparsity, and outperforms the distributed SBL variant proposed in [18] for homogeneous learning.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…Consequently, the algorithm converges fast while having a fixed communication load on the network. As we will show, using simulations and real data studies, the proposed algorithm performs on par with the centralized versions in terms of normalized mean squared error (NMSE) and parameter sparsity, and outperforms the distributed SBL variant proposed in [18] for homogeneous learning.…”
Section: Introductionmentioning
confidence: 93%
“…[17], where a distributed estimate is calculated by loopy belief propagation. In [18] another version of a decentralized SBL method is presented, where an ARD version of SBL is implemented. Its key feature is guaranteed convergence.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides leading to a simple least squares problem, the design of the CEV FIR filter can also be computed distributively. Given that each node knows the desired filter response and the graph shift operator (i.e., the network structure), it can be shown that by reordering the columns of Ψ and the entries of θ the framework of splitting-over-features [37] can be employed for a decentralized estimation of θ.…”
Section: Filter Designmentioning
confidence: 99%